2017
DOI: 10.15666/aeer/1501_563571
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fertilization and Seed Size on Nodulation, Yield and Yield Components of Chickpea (Cicer Arietinum L.)

Abstract: Abstract. This study investigated the effects of seed size and fertilizer usage with seed at planting on agronomic parameters of chickpea as a winter crop. The experiment was conducted according to splitsplit plots of randomized blocks with four replications. As factorial two chickpea varieties (Arda and Diyar 95), two fertilizer applications (with and without fertilizer) and three seed sizes (large, medium and small) are discussed in this study. The results showed that fertilizer applications along with seed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
2
5
0
Order By: Relevance
“…The results confirmed UFPI-38 and UFPI-59 as more efficient rhizobia, mainly with large seeds. In addition, the highest values of parameters were reported in large seeds and it agrees with previous studies assessing the effect of seed size on plant growth and nodulation (DOBERT & BLEVINS 1993;SINGH and WRIGHT,2002;ERDEMCI et al, 2017). Since large seeds present higher reserve content, it could promote faster emergence and more vigorous seedling (SINGH and WRIGHT, 2002).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The results confirmed UFPI-38 and UFPI-59 as more efficient rhizobia, mainly with large seeds. In addition, the highest values of parameters were reported in large seeds and it agrees with previous studies assessing the effect of seed size on plant growth and nodulation (DOBERT & BLEVINS 1993;SINGH and WRIGHT,2002;ERDEMCI et al, 2017). Since large seeds present higher reserve content, it could promote faster emergence and more vigorous seedling (SINGH and WRIGHT, 2002).…”
Section: Discussionsupporting
confidence: 89%
“…Plant traits also influence nodulation and BNF in legumes. Among these traits, seed size contributes for increasing or decreasing the process of N fixation (DOBER &TBLEVINS, 1993;SINGH and WRIGHT, 2002;ERDEMCI et al, 2017). According to ERDEMCI et al (2017) seed size influences seedling vigor and plant growth and large seeds usually produce more vigorous seedlings than small ones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, spacing and N affected nodule numbers and fresh weight, they had a positive correlation with amount of rainfall increasing over LR18 compared to LR17 and SR17 by over 77 and 11% for both correspondingly. Significant interactions were noted in VN and SN, In agreement is Erdemci et al (2017) who noted similar interactions in chickpeas. Worku and Astatkie (2015) reported insignificant results of VS on soybean which is similar to this study.…”
Section: Number Of Nodules and Nodule Fresh Weightsupporting
confidence: 88%
“…Hojjat (2011) also reported that the germination parameters were significantly related by seed weight and large seeds germinated early and showed better germination than small seeds of lentil genotypes. Studies of Erdemci et al (2017) on chickpea showed that large seeds of chickpea had high germination percentage, more seedling dry weight and better electrical conductivity as compare to small seeds. However (Rezapour et al, 2013) in their research about seed size on soybean germination, showed that medium seeds had higher germination percentage than that for large and small seed sizes, but there was not a significant effect of seed size on germination rate.…”
Section: Introductionmentioning
confidence: 99%